Rapid optimisation of cellulolytic enzymes ratios in Saccharomyces cerevisiae using in vitro SCRaMbLE - Elizabeth L. I. Wightman; Heinrich Kroukamp; Isak S. Pretorius; Ian T. Paulsen; Helena K. M. Nevalainen (Biotechnology for Biofuels, 2020)
Abstract Background For the economic production of biofuels and other valuable products from lignocellulosic waste material, a consolidated bioprocessing (CBP) organism is required. With efficient fermentation capability and attractive industrial qualities, Saccharomyces cerevisiae is a preferred candidate and has been engineered to produce enzymes that hydrolyze cellulosic biomass. Efficient cellulose hydrolysis requires the synergistic action of several enzymes, with the optimum combined activity ratio dependent on the composition of the substrate. Results In vitro SCRaMbLE generated a library of plasmids containing different ratios of a β-glucosidase gene (CEL3A) from Saccharomycopsis fibuligera and an endoglucanase gene (CEL5A) from Trichoderma reesei. S. cerevisiae, transformed with the plasmid library, displayed a range of individual enzyme activities and synergistic capabilities. Furthermore, we show for the first time that 4,6-O-(3-ketobutylidene)-4-nitrophenyl-β-d-cellopentaoside (BPNPG5) is a suitable substrate to determine synergistic Cel3A and Cel5A action and an accurate predictive model for this synergistic action was devised. Strains with highest BPNPG5 activity had an average CEL3A and CEL5A gene cassette copy number of 1.3 ± 0.6 and 0.8 ± 0.2, respectively (ratio of 1.6:1). Conclusions Here, we describe a synthetic biology approach to rapidly optimise gene copy numbers to achieve efficient synergistic substrate hydrolysis. This study demonstrates how in vitro SCRaMbLE can be applied to rapidly combine gene constructs in various ratios to allow screening of synergistic enzyme activities for efficient substrate hydrolysis.